2011
DOI: 10.1002/anie.201104544
|View full text |Cite
|
Sign up to set email alerts
|

Use of Hemilabile N,N Ligands in Nitrogen‐Directed Iridium‐Catalyzed Borylations of Arenes

Abstract: The direct activation of unreactive C À H bonds has emerged as a very active field in organic synthesis.[1] One of the best established reactions in this area is the direct borylation of arenes with bis(pinacolato)diboron (B 2 pin 2 ) or pinacolborane (HBpin). After the seminal work by Smith, Hartwig, Miyaura, and their respective co-workers, this method has reached an impressive level of chemical efficiency, [2] mainly because of the introduction of the [Ir(m-X)(cod)] 2 /di-tert-butylbipyridine (dtbpy; X = Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
94
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 173 publications
(103 citation statements)
references
References 42 publications
4
94
0
5
Order By: Relevance
“…Fluoroarenes containing a benzylic hydrosilane group and a benzylic dimethylamine, well-known ortho -directing groups in iridium-catalyzed C–H borylation, 22,23b were selectively borylated ortho to fluorine rather than ortho to these functional groups to yield fluoroarenes 6g and 6h (Scheme 2). In iridium catalysis, benzylic hydrosilanes are proposed to direct ortho -borylation from formation of a putative iridium bis(boryl) silyl intermediate arising from reaction of the silane Si–H bond with the iridium tris(boryl) followed by selective C–H activation (Scheme 3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fluoroarenes containing a benzylic hydrosilane group and a benzylic dimethylamine, well-known ortho -directing groups in iridium-catalyzed C–H borylation, 22,23b were selectively borylated ortho to fluorine rather than ortho to these functional groups to yield fluoroarenes 6g and 6h (Scheme 2). In iridium catalysis, benzylic hydrosilanes are proposed to direct ortho -borylation from formation of a putative iridium bis(boryl) silyl intermediate arising from reaction of the silane Si–H bond with the iridium tris(boryl) followed by selective C–H activation (Scheme 3).…”
Section: Resultsmentioning
confidence: 99%
“…Iridium catalysts containing hemilabile N , N ligands 23a promote ortho -borylation using a benzylic dimethylamine as a directing group. 23b The ortho selectivity is proposed to arise from coordination of the [NMe 2 ] group to the metal followed by dissociation of an amine nitrogen from the supporting N , N chelate, opening a site for C–H activation (Scheme 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[32] The boryl moiety can be subsequently transformed into a bromide using Hartwig´s methodology. [33] This route provides a versatile access to arylbromides that can be converted into the target compounds by a bromide-lithium exchange at 78 C, followed by trapping of the lithiated species with (Mes)2BF (Scheme 2).…”
Section: Syntheses and Nmr Spectroscopic Characterizationmentioning
confidence: 99%
“…[1],[2] Similarly, it has been shown that directing groups can alter regioselectivities in Ir-catalyzed C–H borylations. [3] Examples fall into two classes: (i) those where the directing group is already present in the substrate, [4] and (ii) those where it must be installed. [5] An example of the latter class is Hartwig’s use of silylhydrides to facilitate the borylation ortho to OH and NH functionality and effect the functionalization at sp 2 positions in arylsilanes.…”
mentioning
confidence: 99%